TAKSONOMI POLYPODIACEAE DITINJAU DARI TYPE STOMATA - Joko Ariyan (Universitas Sebelas Maret, 2014)
Abstract - The research of Polypodiaceae taxonomy viewed by stomata types was conducted in Kaliurang Yogyakarta. The purpose of the research is to know is stomata type can be used as based of Polypodiaceae classification.The first step of the research was collected species of Polypodiaceae in Kaliurang. The second step was identified their stomata types and then compared the grouping of species based on their stomata type to grouping of species based on their classification. The conclution of the research is stomata type can’t be used as (don’t similar with) Polypodiaceae classification. Keywords: Polypodiaceae, stomata types, taxonomy